2020
DOI: 10.1002/alr.22486
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and outcomes of endoscopic sinus surgery after endoscopic skull‐base surgery

Abstract: Background Patients undergoing endoscopic resection of neoplasms with both sinonasal and skull base involvement can develop chronic rhinosinusitis (CRS) after treatment and may occasionally benefit from additional endoscopic sinus surgery (ESS). We investigate risk factors and outcomes associated with revision ESS (rESS) after endoscopic skull‐base surgery (SBS) for neoplasms with combined sinonasal and skull base involvement. Methods A retrospective review of patients with neoplasms with both sinonasal and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In addition to that, SNOT-22 is commonly used in assessing QOL after endoscopic surgery for benign disease such as chronic rhinosinusitis [8 ▪ ,20,21] (Table 3). Although it lacks questions related to skull base, it has been previously used to assess postoperative QOL in patients undergoing endonasal surgery for sinonasal and skull base tumors, showing significant improvement in sinonasal morbidity [22 ▪ ,23–25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, SNOT-22 is commonly used in assessing QOL after endoscopic surgery for benign disease such as chronic rhinosinusitis [8 ▪ ,20,21] (Table 3). Although it lacks questions related to skull base, it has been previously used to assess postoperative QOL in patients undergoing endonasal surgery for sinonasal and skull base tumors, showing significant improvement in sinonasal morbidity [22 ▪ ,23–25].…”
Section: Introductionmentioning
confidence: 99%
“…From a radiographic standpoint, Shah et al performed a retrospective review of the adult population undergoing endoscopic skull base surgery and found that up to 18% of patients developed CRS requiring intervention. 15 Langdon et al demonstrated statistically significant increases in pre-and six month post-operative Lund-MacKay scores. 13 McCoul et al found that SNOT-22 scores were significantly higher in patients who underwent endoscopic skull base surgery at three weeks compared to baseline (17.5 vs. 27.8, p = 0.001), and gradually return to pre-operative scores at six weeks, 12 weeks, and six months (23.6, 22.2, and 16.2, respectively).…”
Section: Discussionmentioning
confidence: 96%
“…Although there is a lack of data in the pediatric population, there have been reports in the adult population which may provide insights in this domain. From a radiographic standpoint, Shah et al performed a retrospective review of the adult population undergoing endoscopic skull base surgery and found that up to 18% of patients developed CRS requiring intervention 15 . Langdon et al demonstrated statistically significant increases in pre‐ and six month post‐operative Lund‐MacKay scores 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations